Uji Kemampuan Beberapa Isolat Rhizobakteria untuk Meningkatkan Pertumbuhan dan Hasil Kedelai (Glycine Max (L)Merill) - LESTIANINGRUM, AYU GEK MIRAH; RAKA, I GUSTI NGURAH; NYANA, I DEWA NYOMAN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.6, No.1, Januari 2017, 2017)
Test Capabilities some Isolate Rhizobacteria for Enhancing the Growth and Yield of Soybean (Glycine max L. Merill) This study aims to get the isolates of rhizobacteria that have a better ability to increase growth and yield of soybean. Randomized block design was used with 14 treatments, which 13 are treated using rhizobacteria isolates from different plants root and one without isolates of rhizobacteria. Each treatment was repeated three times. This research was conductedin the pots with observations of the growth and yield of soybean that includes; plant height, leaf number, number of branches, chlorophyll, the number of nodules, dry weight of the plant part above the ground and below the ground, the number of pods, number of seeds, seed weight, and predict the outcome of soybeans per hectare. The result showed that three isolates rhizobacteria who have better abilities compared to other isolates rhizobacteria to improve the growth and yield of soybean that isolates R53, R6, and R26, with its ability to improve; plant height, number of branches, number of leaves, chlorophyll, the number of nodules, the number of dry weight of the plant above ground or below ground, the number of pods, number of seeds, seed weight and better ability to increase soybean yield per hectare. In addition to these three isolates are also two isolates rhizobakteria which only has the ability to increase soybean yield that isolates R10 and R11. The five isolates rhizobakteria ( R53, R6, R26, R10, dan R11 ) can be regarded as rhizobateria were able to spur the growth and yield soy called PGPR bacteria .
Keywords: Soybean, rhizobacteria, results and PGPR